Bridging the Divide - Khan, Sajidah (SA Heart Journal, 2017)
The theme for the 2014 congress “Bridging the Divide” was selected to highlight the idea that improving the overall health of a population requires partnerships and interdependence with structures within and outside the healthcare domain. A health care delivery system is thought to account for around 10% of preventable deaths with the remainder attributable to social and environmental determinants, personal behaviour and genetic predisposition.(1) This interdependence comes from the knowledge that increased life expectancy, on the one hand due to a reduction in premature mortality from improved sanitation, nutrition and vaccinations in the childhood years, at the other end is linked to the health and survival of the elderly due to innovations in science and technology.